Examination of Water Quantification and Incorporation in Transition Zone Minerals: Wadsleyite, Ringwoodite and Phase D Using ERDA (Elastic Recoil Detection Analysis) - Bolfan-Casanova, Nathalie; Schiavi, Federica; Novella, Davide; Bureau, Hélène; Raepsaet, Caroline; Khodja, Hicham; Demouchy, Sylvie (Frontiers in Earth Science, 2018)
Hydrous wadsleyite, ringwoodite and phase D have been synthesized in the MgO-SiO2-H2O and MgO-FeO-SiO2-H2O systems at mantle transition zone conditions (15-21 GPa and 1100-1700 °C) to investigate their water incorporation using Elastic Recoil Detection Analysis (ERDA), which is an absolute quantitative method. Wadsleyite and ringwoodite water contents vary from 0.1 to 3.2 wt % H2O and for ringwoodite containing up to 1.16 wt% H2O we observe that the (Mg+Fe)/Si ratio versus water content follows the same trend as for wadsleyite, indicating that H is substituting for Mg as for wadsleyite. We also measured, for the first time, the water content of phase D and observed that it varies from 6.7 to 11.2 wt% H2O, up to twice less than estimated from electron microprobe analysis totals Using these experiments, we were able to determine the absorptivity coefficient for OH infrared absorption bands in four wadsleyite samples and five ringwoodite samples. The average for the two iron-free wadsleyite samples leads to an absorptivity of 69000 +/- 7000 L/moles H2O/cm2, in very good agreement with previous determinations. The wadsleyite with 8 mole% Fe displays an absorptivity of 67000 +/- 5000 L/moles H2O/cm2. The absorptivity values vary from 116400 +/- 4200 for Fe-free ringwoodite to 137700 +/- 8900 for Fe-bearing ringwoodite (10% mole Fe). Our results show that absorptivity coefficient for OH infrared absorption of ringwoodite do not drastically change with Fe content and that the frequency-based calibration of Paterson (1982) under-estimates its water determinations by 50%. This is very important to know when comparing data from different studies where different extinction coefficients have been used.